Assessing population exposure to coastal flooding due to sea level rise - Mathew E. Hauer (Nature Portfolio, 2021)
The exposure of populations to sea-level rise is a leading indicator assessing the impact of future climate change on coastal regions. The authors identify three spatial zones of flooding such as mean higher water, the 100 year floodplain and the low-elevation coastal zone and show population exposure can differ between those zones.